Phenomenological Implications of Modified Loop Cosmologies: An Overview - Li, Bao-Fei; Singh, Parampreet; Wang, Anzhong (Frontiers in Astronomy and Space Sciences, 2021)
In this manuscript, we first provide a brief review of the effective dynamics of two recently well-studied models of modified loop quantum cosmologies (mLQCs) which arise from different regularizations of the Hamiltonian constraint and show the robustness of a generic resolution of the big bang singularity which is replaced by a quantum bounce due to non-perturbative Planck scale effects. As in loop quantum cosmology (LQC), in these modified models the slow-roll inflation happens generically. We consider the cosmological perturbations following both the dressed and the hybrid approaches and clarify some subtle issues regarding the ambiguity of the extension of the effective potential of the scalar perturbations across the quantum bounce, and the choice of initial conditions. Both of the modified regularizations yield consistency of the predicted primordial power spectra with current observations for the Starobinsky inflation potential for dressed as well as hybrid approaches. But difference in primordial power spectrum result between different regularizations and LQC. In addition, for mLQC-I, striking differences arise for the dressed and hybrid perturbation approaches in the infra-red and oscillatory regimes. While the differences between regularizations can be attributed to differences in Planck scale scale physics, and different permissible choices of the initial conditions, the differences between the two perturbation approaches which are tied to underlying assumptions have been reported for the first time. These differences between regularizations and approaches can be observable at the level of non-Gaussianities.